Influence of family, resilience and peers on deviant behaviour of youth in Melaka/ Abu Hanifah Mohd Said - Mohd Said, Abu Hanifah (Faculty of Business and Management, 2013)
Youth are the important segment because youth are the backbone of a nation. As a social political force, youth are a power to reckon with. Youth are very important segment of Malaysian society. Based on Department Of Statistic data, the number of the Malaysian people between the ages of 15-40 years are reached more than 13,37 million. This means that over 45.6% Malaysian’s populations are youth. The women youth in Malaysian is 6,411.7 million compare to men youth only 5,965.4.This study was aimed to identify the most influential factor that contribute toward youth deviance behaviours in Melaka. 200 respondents were chosen from different district around Melaka such as Melaka Tengah, Jasin and also Alor Gajah to complete the questionnaire of three elements of factor such as family, peers and also resilience of youth itself toward deviance behaviour. The result from Pearson Correlation that shows the peers are more influence the youth in order to do a deviance behaviours. The family and resilience also still have a relationship with deviance behaviours and the hypotheses toward three of the independent variable are accepted. This issue shall be discussing to reduce the number of youth from joining or do deviance behaviours because the youth are a crucial part of Malaysian society. They play an important role in society today. And the changes of Malaysian demographic and technological landscape, they are going to play even more important role in the future.